Deputies of the State Duma of the VI Convocation: Social-Professional Sources of Recruitment - Denis Tev (Journal of Economic Sociology, 2017)
The article examines the social and professional composition of the State Duma of the sixth convocation. The purpose of the study is to identify and analyze the socio-professional categories that serve as sources of recruitment for the deputy corps. As a theoretical basis, a wide range of works by domestic and foreign authors devoted to recruiting the political elite was used. The method of investigation can be defined as a structuralbiographical analysis. The empirical basic research is a database, which includes biographical information about 532 parliamentarians who worked in the State Duma of the sixth convocation. The sources of data arranged in personal questionnaires and then processed statistically were websites of state bodies, commercial structures, and biographical Internet portals. The study showed that the political elite of the Russian Federation are substantially rooted in the structures of the political and administrative power of Soviet society: Among the deputies of the State Duma, the nomenclature experience is more common to a greater extent than for the administrative and economic elites of the country. The important trend in the post-Soviet career of deputies is political professionalization. A noticeable trend is the bureaucratization of the deputy corps, many of whom worked in the post-Soviet period in administrative structures. There is dynamic interlocking between the federal administrative and the political elites, especially at the level of the Duma leadership. Quite pronounced is the militarization of the political elite, although there are fewer people from the force structures than in the administrative elite. Business is a most important source of recruitment of the political elite outside the political and administrative structures. Although there are few descendants from large nationwide businesses, interlocking of the country’s economic and political elites does take place. Finally, some professional categories widely represented in the legislatures of a number of Western countries—lawyers and educators—are rather poorly presented in the Duma. The author concludes that these recruitment tendencies can, on the one hand, be related to the specifics of the political and economic organization of Russian society (the weakness of the parliament, “crony capitalism”, etc.), and, on the other hand, influence the political attitudes and behaviors of legislators (including their attitude regarding the Soviet past, the political regime, and the interests of various social groups).